CONTEMPORARY CHALLENGES IN LEGAL MANAGEMENT: RESPONDING TO CHANGING REGULATIONS AND BUSINESS NEEDS - Rita Hayati; E. Caroline; Mokhamad Eldon (ADISAM Publisher, 2025)
The era of digitalization has made many changes in the world of business and law. The digital revolution and technological innovations are creating new challenges for existing rules. Issues such as artificial intelligence, blockchain, and the Internet of Things require regulations that can adapt quickly. Globalization also increases the complexity of managing law as companies must comply with various rules in different countries. In addition, social and environmental responsibility is becoming increasingly important. Companies are required to act ethically while protecting the rights of society and the environment. Data privacy is another major issue demanded by regulations such as GDPR. This demands stricter cyber risk management. The implication is that legal management must be more responsive and strategic. Collaboration between business units needs to improve. Investment in legal and governance professionals is also critical. Amidst these complex and dynamic challenges, legal management is required to ensure legal compliance and support the company's strategic objectives.